TRANSLATION TECHNIQUES IN AND ACCURACY OF THE INDONESIAN SUBTITLES OF THE MOVIE PHILOMENA - Latif, Muhammad Abdul (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
This descriptive qualitative study describes the translation techniques and the accuracy of the dialogs found in the movie Philomena. The purposes of this study are to find out the translation techniques in and the accuracy of the Indonesian subtitle in its dialogs. The data of this study are English-Indonesian translations and the result accuracy rating instruments. The translation techniques applied to translate the Indonesian subtitle are determined and are later analyzed to find out the degree of accuracy of the Indonesian version. The result of the study showed that there are eighteen translation techniques used in the Indonesian subtitle. They are literal translation, reduction, amplification, established equivalent, linguistic compression, borrowing, transposition, calque, compensation, modulation, particularization, discursive creation, linguistic amplification, generalization, adaptation, substitution, description, and variation. The accuracy level is 97.89%.